[Co(TPP)]‐Catalyzed Formation of Substituted Piperidines - Lankelma, Marianne; Olivares, Astrid M.; de Bruin, Bas (Chemistry : a European journal, 2019)
Radical cyclization via cobalt(III)‐carbene radical intermediates is a powerful method for the synthesis of (hetero)cyclic structures. Building on the recently reported synthesis of five‐membered N‐heterocyclic pyrrolidines catalyzed by CoII porphyrins, the [Co(TPP)]‐catalyzed formation of useful six‐membered N‐heterocyclic piperidines directly from linear aldehydes is presented herein. The piperidines were obtained in overall high yields, with linear alkenes being formed as side products in small amounts. A DFT study was performed to gain a deeper mechanistic understanding of the cobalt(II)‐porphyrin‐catalyzed formation of pyrrolidines, piperidines, and linear alkenes. The calculations showed that the alkenes are unlikely to be formed through an expected 1,2‐hydrogen‐atom transfer to the carbene carbon. Instead, the calculations were consistent with a pathway involving benzyl‐radical formation followed by radical‐rebound ring closure to form the piperidines. Competitive 1,5‐hydrogen‐atom transfer from the β‐position to the benzyl radical explained the formation of linear alkenes as side products. Macrocyclic ligands for heterocyclic products: Radical cyclization via cobalt(III)‐carbene radical intermediates is a powerful method for the synthesis of (hetero)cyclic structures. Building on the recently reported synthesis of five‐membered pyrrolidine rings catalyzed by CoII amidoporphyrins, the [Co(TPP)]‐catalyzed (TPP=tetraphenylporphyrin) formation of six‐membered piperidine rings, which was found to be accompanied by formation of small amounts of linear alkenes, is reported herein. A DFT study was also performed to gain a deeper mechanistic understanding.